An Analysis of Figurative Language in Ariana Grande’s Album “Thank U, Next” - Deni Arnita Hulu; Elia Nova Sembiring; Natalia Widya Pasca Tarigan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study analyzes the figurative language (simile, metaphor, personification, hyperbole, symbol, irony and idiom) in the song lyrics. This study also aims to determine the most dominant type of figurative language and then to identify the themes of the twelve songs in the song lyrics of Ariana Grande's album